2017
DOI: 10.1002/asia.201700801
|View full text |Cite
|
Sign up to set email alerts
|

A Nanosized Gly‐Decorated Praseodymium‐Stabilized Selenotungstate Cluster: Synthesis, Structure, and Oxidation Catalysis

Abstract: A flexible one-pot strategy with pyramidal Se heteroatoms was employed for the assembly of the praseodymium-containing gly-decorated polyoxotungstate [{Pr (H O) [Se W O (gly) ]} (Se W O H )] (1 a), which is constructed from one {Se W O H } unit and two identical {Pr (H O) [Se W O (gly) ]} units. Furthermore, the catalytic performance of Cs Na H [{Pr (H O) [Se W O (gly) ]} (Se W O H )]⋅25 H O (1) for alkene epoxidation with hydrogen peroxide was investigated under mild reaction conditions, and the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Recently, the pursuit of novel inorganic–organic hybrid REISTs (IOHREISTs) by continuously introducing RE cations and organic functional ligands into the ST system has appealed to researchers due to REISTs’ outstanding latent applications in catalytic, magnetic, and photoelectric fields. Even though much effort has been devoted to this research, only a few examples of IOHREISTs have been reported. Representatively, a case of glycine-modified tripraseodymium-implanted ST was obtained by Niu et al in 2017 . Moreover, acetate-modified cerium-encapsulated STs have been obtained by our group, which can function as candidates for electrochemical detection of dopamine and paracetamol .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the pursuit of novel inorganic–organic hybrid REISTs (IOHREISTs) by continuously introducing RE cations and organic functional ligands into the ST system has appealed to researchers due to REISTs’ outstanding latent applications in catalytic, magnetic, and photoelectric fields. Even though much effort has been devoted to this research, only a few examples of IOHREISTs have been reported. Representatively, a case of glycine-modified tripraseodymium-implanted ST was obtained by Niu et al in 2017 . Moreover, acetate-modified cerium-encapsulated STs have been obtained by our group, which can function as candidates for electrochemical detection of dopamine and paracetamol .…”
Section: Introductionmentioning
confidence: 99%
“…Representatively, a case of glycine-modified tripraseodymium-implanted ST was obtained by Niu et al in 2017. 22 Moreover, acetate-modified cerium-encapsulated STs have been obtained by our group, which can function as candidates for electrochemical detection of dopamine and paracetamol. 24 Nevertheless, the flexible H 4 tart with two hydroxyl groups and two terminal carboxyl groups has not been reported in the construction of IOHREISTs, even though there are four potential coordination sites in its structure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is noticeable that in this work acetate groups as organic constituents modify the POA structure of 1 . Among them, acetate groups can be coordinated with not only the Ce1 3+ cation, but also two W centers in each {W 2 O 11 } unit because of the appropriate location and steric hindrance. , Above all, two acetate groups as linkers combine two adjoining W atoms. Such a phenomenon in which an acetate group directly bridges two W centers is unusual in POM chemistry, which provides a great likelihood of constructing carboxyl bridging polyoxo-tungstates and gives us extreme enlightenment and a high level of inspiration to expore and fabricate novel carboxylated POMs by selecting appropriate organic carboxylic acid ligands.…”
Section: Resultsmentioning
confidence: 99%
“…The Se IV heteroatom contains a pair of lone electrons, so the pyramidal SeO 3 2– group can serve as a template for constructing POM-based open-framework SeTs and further concatenating with different sorts of metals to form diverse structures. Earlier studies (before 2016) were focused on the “pure” SeTs and TM-substituted SeTs. In the last decade, Ln-containing POMs have drawn incremental attention on account of the excellent luminescence properties of Ln cations. , Compared with TM ions, Ln ions have abundant coordination modes and intense oxophilicity, making it easy for them to capture lacunary POM fragments to expand structural diversity. In the last 5 years, research has been focused on Ln-substituted SeTs (LnSSeTs). The first LnSSeTs are the octameric nanoclusters reported by Su’s group, which could be self-assembled to hollow spheres in dilute solution, and the electrochemical and magnetic properties of these LnSSeTs were investigated . We have devoted ourselves to synthesizing LnSeSTs and achieved some prominent results. Typically, trimeric and hexameric LnSSeTs have been isolated in the presence of different organocations.…”
Section: Introductionmentioning
confidence: 99%
“…Selenotungstates, as an essential subfamily of POTs, have attracted immense concern in recent years. It is possible to control the size, nuclearity, and connectivity of BBs in situ by a SeO 3 2– template with its powerful structure-directing effect; thus, its structural versatilities may be realized at the fragment level. Many groups have gained mentionable achievements on the synthesis and functionalization of “pure” or transition-metal-substituted species in the past decade. Recently, our group found first Ln-containing selenotungstates by combining Ce ions with SeO 3 2– heteroanion templates; however, this field still possesses less progress because the reported Ln ions are mainly focused on early-Ln ions (a detailed survey of the Ln-containing selenotungstates is given Table S1). With regard to magnetic behaviors, integration of the intrinsically large magnetic anisotropy and large ground-state spin values owned by Gd or Dy ions under rigidity and insulating Se-templated POT ligand fields may be possible to bring slow relaxation of magnetization to such a molecular system, which holds potential applications in memory-storage systems or quantum computation. ,,, Thus, the development of mid-Ln-containing selenotungstates may give rise to more complicated and unprecedented architectures with special magnetic functionalities.…”
Section: Introductionmentioning
confidence: 99%